Answer:
60
Step-by-step explanation:
60/4=15
15>7
The average rate of change of the function from x = 0 to x = 2 is -2
From the complete question (see attachment), we have the following ordered pair when x = 0 and x = 2
![(x,y) = \{(0,10)\ (2,6)\}](https://tex.z-dn.net/?f=%28x%2Cy%29%20%3D%20%5C%7B%280%2C10%29%5C%20%282%2C6%29%5C%7D)
The average rate of change is calculated using:
![\Delta x = \frac{y_2 -y_1}{x_2 -x_1}](https://tex.z-dn.net/?f=%5CDelta%20x%20%3D%20%5Cfrac%7By_2%20-y_1%7D%7Bx_2%20-x_1%7D)
So, we have:
![\Delta x = \frac{6-10}{2-0}](https://tex.z-dn.net/?f=%5CDelta%20x%20%3D%20%5Cfrac%7B6-10%7D%7B2-0%7D)
Evaluate common terms
![\Delta x = \frac{-4}{2}](https://tex.z-dn.net/?f=%5CDelta%20x%20%3D%20%5Cfrac%7B-4%7D%7B2%7D)
Divide -4 by 2
![\Delta x = -2](https://tex.z-dn.net/?f=%5CDelta%20x%20%3D%20-2)
Hence, the average rate of change of the function from x = 0 to x = 2 is -2
Read more about rate of change at:
brainly.com/question/8728504
Answer:
11 years old
Step-by-step explanation:
3 years ago, Gloria was 32 years old
If Ivana's age is = x
Then, 4x = 32
x = 8
3 years ago, Ivana was 8 years old
So now she is 11 years old.
Take the square root of both sides of both sides of the equation. Doing this finds your answer, 16.